Coaching behaviour in elite sport in Japan: a coaching perspective - Yoko, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
The purpose of this study to analyse the behavioural characteristics of elite Japanese coaches and clarify the coaches` educational factors. Participants were four elite sports coaches (three men and one woman). To be included in the study, coaches were required to have worked with, or to be currently working with Olympic-level athletes. The interview guide comprised of three sections: coaching behaviour in training; coaching behaviour in competition; and athlete`s skills related to coaching behaviour and summary questions. Findings revealed 11 higher-order themes, which we categorised into the following four general dimensions: analysis of situation and information (getting the latest information, social context); interpersonal relationships (teaching ability of a coach depending on the athletes` skill levels, communication, team atmosphere); intrapersonal knowledge (external self-awareness, internal self-awareness); professional knowledge (athlete safety, competitive performance, competition preparation, training performance).